CXCR4 engagement triggers CD47 internalization and antitumor immunization in a mouse model of mesothelioma - Rosanna Mezzapelle; Francesco De Marchis; Chiara Passera; Manuela Leo; Francesca Brambilla; Federica Colombo; Maura Casalgrandi; Alessandro Preti; Samuel Zambrano; Patrizia Castellani; Riccardo Ertassi; Marco Silingardi; et al. (EMBO Molecular Medicine)
Abstract Boosting antitumor immunity has emerged as a powerful strategy in cancer treatment. While releasing T‐cell brakes has received most attention, tumor recognition by T cells is a pre‐requisite. Radiotherapy and certain cytotoxic drugs induce the release of damage‐associated molecular patterns, which promote tumor antigen cross‐presentation and T‐cell priming. Antibodies against the “do not eat me” signal CD47 cause macrophage phagocytosis of live tumor cells and drive the emergence of antitumor T cells. Here we show that CXCR4 activation, so far associated only with tumor progression and metastasis, also flags tumor cells to immune recognition. Both CXCL12, the natural CXCR4 ligand, and BoxA, a fragment of HMGB1, promote the release of DAMPs and the internalization of CD47, leading to protective antitumor immunity. We designate as Immunogenic Surrender the process by which CXCR4 turns in tumor cells to macrophages, thereby subjecting a rapidly growing tissue to immunological scrutiny. Importantly, while CXCL12 promotes tumor cell proliferation, BoxA reduces it, and might be exploited for the treatment of malignant mesothelioma and a variety of other tumors.